Squash Varieties Domesticated for Different Purposes Differ in Chemical and Physical Defense Against Leaf and Root Herbivores - Jaccard, Charlyne; Cuny, Maximilien A. C.; Bustos-Segura, Carlos; Arce, Carla C. M.; Giollo, Lorenzo; Glauser, Gaetan; Benrey, Betty (Frontiers in Agronomy, 2021)
Plant domestication often reduces plant defenses by selection on chemical and physical defense traits. Thus, it is expected that herbivorous insects perform better on crop varieties than on their wild relatives. However, recent studies show that this pattern is not ubiquitous. We examined how varieties of squash (Cucurbita spp.) domesticated for different purposes (for consumption or as ornamentals), differ in plant defense traits and in their interactions with a leaf and a root herbivore. Two types of defenses were measured: cucurbitacins, which are toxic phytochemicals, and trichomes that are physical barriers for most herbivores. We addressed the following questions: i) what is the variation in cucurbitacin content and leaf trichome density among varieties? ii) does purpose of domestication explain differences in defense traits among varieties? and iii) are herbivore feeding preferences and performance altered by the defense traits of squash varieties? We found great variation in cucurbitacin content among varieties, but not according to their purpose of domestication. Cucurbitacins were found mostly in cotyledons and roots and in very small quantities in the leaves. In contrast, trichome density was greater on the varieties selected for consumption than on the ornamental varieties. The performance of a leaf herbivore (Spodoptera latifascia) and a root herbivore (Diabrotica balteata), was not different among squash varieties. Moreover, in a choice experiment, larvae of the root herbivore preferred to feed on squash varieties with high cucurbitacin content. Whereas in the field, native leaf herbivores preferred to feed on varieties selected for consumption. Our results contribute to a better understanding on how varietal selection may differentially affect plant defenses. This knowledge could help in the development of crop varieties with enhanced insect resistance.